FAKTOR-FAKTOR TATA KELOLA ARSIP PADA DINAS PUPR KOTA SUNGAI PENUH - Oktovianus, YZ; Zulherman, Zulherman; Jumas, Dwifitra Y (SIGMA TEKNIKA, 2025)
Archives and archiving can be optimally beneficial if managed properly, but on the contrary if archives are not managed properly then it can cause problems. This study aims to identify, analyze factors and variables of archive governance of the PUPR Office of Sungai Penuh City. The research method uses a quantitative method, where data collection uses a questionnaire, while data processing is carried out using SPSS (Statistical Package for the Social Sciences). Validation, reliability, KMO Bartlett's test and factor analysis with Confirmatory Factor Analysis were carried out on the results of the questionnaire. The results of the study indicate that there are factors that influence the governance of archives of the PUPR Office of Sungai Penuh City, namely equipment and resource factors, administration and expertise factors, information and storage factors. This is evidenced by the stages of analysis carried out for the KMO test having met the requirements with a KMO value of 0.814 or greater than 0.5 and Bartlett's 0.000 or less than 0.005 so that it is stated that there is eligibility for the variables used for the analysis process. The dominant factors influencing archive management at the PUPR Service of Sungai Penuh City are administration and expertise factors with an average value of the variables forming the analysis factors of (4.19).